Edukasi Pentingnya 1000 Hari Pertama Kehidupan Dalam Meningkatkan Kesehatan Ibu Hamil Dan Balita Di Puskesmas Pakusari Dan Ledokombo, Jember - Rosida Hari (LP2M Universitas Jember, 2023)
The 1000 First Days of Life is the early period of life when you are still in the womb up to the first 2 years of life. The focus of handling nutrition in the 1000 First Day of Life is to prevent malnutrition as a major health problem in toddlers because it can hinder the process of growth and contribute to child morbidity and mortality. Based on this, community service activities were carried out with the topic